Genetic analysis and identification of the candidate genes of maize resistance to Ustilago maydis by BSA-Seq and RNA-Seq - Jingyi Wang; Wenqing Zhao; Fangguo Chang; Haicheng Yang; Fangju Jiao; Fang Wang; Yunling Peng (BMC Plant Biology)
Abstract Maize common smut is a common disease caused by Ustilago maydis, can cause serious damage to the yield and quality of maize. To elucidate the genetic mechanism of resistance to maize smut disease, and to discover the relevant resistance genes, which have important scientific implications for maize resistance breeding. This study used the high-resistance maize variety Qi319 and the high-susceptibility variety Ye478 as materials, and constructed different segregating populations through hybridization, backcrossing, and other methods. Through field artificial inoculation and disease resistance identification, the six population (P1, P2, F1, F2, BC1P1, BC1P2) constructed was subjected to genetic and correlation analysis using a plant "quantitative trait main gene + multi gene mixed genetic model". The results showed that the optimal genetic model for maize resistance of U. maydis is MX2-ADI-ADI, the resistance of maize to U. maydis was mainly controlled by two pairs of additive-dominant-superior main genes + additive-dominant-superior polygenic genes. The heritabilities of major genes of F2, BC1P1 and BC1P2 were 69.24%, 57.89% and 54.09%, respectively, indicating that the resistance of the variety Qi319 to U. maydis was transmitted steadily to the progeny. The resistance/susceptibility pool was constructed from F2 population constructed by parents, a total of 6 candidate intervals were located on chromosomes 4, 6, 7 and 10, with a total length of 51.23Mb and containing 3723 genes by BSA-seq analysis. Transcriptome sequencing analysis showed that photosynthesis, plant pathogen interaction, carbon sequestration of photosynthetic organisms, plant hormone signal transduction, MAPK signal transduction and other pathways may be involved in the metabolic regulation of Qi319 resistance to U. maydis. The results laid a theoretical foundation for analyzing the molecular mechanism of maize resistance to powdery mildew and cloning the resistance gene.